Analysis of Acid Drainage Flow Zones in a Rocky Massif in a Uranium Mine from Structural and Geophysical Diagnoses - Camarero, Pedro Lemos [UNESP]; Moreira, César Augusto [UNESP]; Targa, Débora Andrade [UNESP]; Duz, Beatriz Guzzo [UNESP]; Pereira, Henrique Garcia (Springer Nature, 2021)
During its 13 years of non-continuous operation, the Osamu Utsumi Mine has generated serious environmental impacts. This mining complex is now attempting to decommission this uranium mine to reduce its environmental liabilities. As part of a hydrogeological analysis of the old Osamu Utsumi Mine pit area, a geophysical investigation was carried out along each front of the mine pit using electrical resistivity tomography and a dipole–dipole array. The lithology described in each front, the physical access, and data from monitoring wells also contributed to the geophysical interpretation and, hence, the hydrogeological analysis. The field results and geochemical data from monitoring wells enabled us to distinguish areas where water was flowing through fractures in the massif and areas with more acidic water, with electrical resistivity values less than 15 Ω m.
Análisis de las zonas de flujo de drenaje ácido en un macizo rocoso de una mina de uranio a partir de diagnósticos estructurales y geofísicos
Keywords: DC resistivity; Electrical resistivity tomography; Fractured aquifer; Hydrogeology; Mine decommissioning; Sulfides